Perilaku Informasi Mahasiswa dalam Perspektif Pengalaman Informasi - Franindya Purwaningtyas (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
Experience which is something that involves developing students' awareness of an event. Information experience as student awareness in interacting with information and types of information both from access, sources and information media. Students who are referred to as the net generation have the characteristics of freedom, customization, scruncity, integrity, collaboration, entertainment, speed and innovation. The student's information experience will be studied intensely and in depth, as a natural process that will refer to the real life of the object or subject to be studied through observation and interviews. Observation of student activities on information behavior in meeting information needs through various media, both conventional media and digital media. The intensity of student interaction with devices or information channels has a significant influence on student information behavior. The information channels used by students also vary from conventional to digital based on the habits of students.